Digital Language Diversity Project Survey Data - Soria, Claudia; Quochi, Valeria; Russo, Irene; Sarhimaa, Anneli; Kruse, Eleonore; Hicks, Davyth; Salonen, Tuomo; Gurrutxaga Hernaiz, Antton; Ceberio Berger, Klara (Istituto di Linguistica Computazionale “A. Zampolli” - Consiglio Nazionale delle Ricerche (ILC-CNR), 2017)
This dataset contains the original responses to a questionaire run in 2016 within the DLDP project about the use and usability of 4 European regional and minority languages on digital media and devices: namely Basque, Breton, Karelian and Sardinian (See http://www.dldp.eu/content/survey-digital-fitness). The majority of questions were closed questions where respondents had to tick a box, occasionally multiple choice was allowed. A few questions required free text provision. The questionnaire was designed using 'Google Forms' and was run on the same platform in the summer 2016. The results of the survey are brielfly presented in the DLDP reports available here: http://www.dldp.eu/content/reports-digital-language-diversity-europe